Case report: Liquid biopsy, the sooner the better? - Thomas, Quentin Dominique; Colard-Thomas, Julien; Delansay, Delphine; Leenhardt, Fanny; Solassol, Jerome; Vendrell, Julie A.; Quantin, Xavier (Frontiers in Oncology, 2022)
The detection of circulating tumor DNA (ctDNA) by liquid biopsy is taking an increasing role in thoracic oncology management due to its predictive and prognostic value. For non-small cell lung cancer, it allows the detection of molecular mutations that can be targeted with tyrosine kinase inhibitors (TKIs). We report the case of a patient with life-threatening hepatocellular failure and thrombotic microangiopathy at the diagnosis. A salvage chemotherapy was attempted, resulting in a major worsening of her general condition and the decision to stop all anti-cancer treatment. The liquid biopsy performed at the time of immunohistochemical non-small cell lung cancer diagnosis revealed within 7 days the presence of an epidermal growth factor receptor (EGFR)DEL19 activating mutation with 736,400 DNA copies/ml of plasma. It was finally decided to attempt a treatment with osimertinib (third generation anti-EGFR TKI) despite the fact that the patient was in a pre-mortem situation. Osimertinib led to a significant and prompt improvement of her performance status after only one week of treatment. The tumor tissue genotyping performed by next-generation sequencing (NGS) was available 10 days after starting TKI treatment. It revealed in addition to the EGFRDEL19 mutation, a JAK3 and EGFR amplification, highlighting the complex interactions between EGFR and the JAK/STAT signaling pathways. The first CT-scan performed after 2 months under osimertinib showed a tumor morphologic partial response. The biological assay showed a major decrease in the EGFRDEL19 mutation ctDNA levels (40.0 copies/ml). The liquid biopsy allowed an early implementation of a targeted therapy without which the patient would probably be dead. Testing for ctDNA should be discussed routinely at diagnosis in addition to tumor tissue genotyping for patient with metastatic non-small cell lung cancer that raise the clinical profile of oncogenic addiction.